2023
DOI: 10.1039/d3dt01707a
|View full text |Cite
|
Sign up to set email alerts
|

Spin-state switching: chemical modulation and the impact of intermolecular interactions in manganese(iii) complexes

Abstract: A series of mononuclear manganese(III) complexes [Mn(X-sal2-323)](ReO4) (X = 5 Cl, 1; X = 5 Br, 2; X = 3,5 Cl, 3; X = 3,5 Br, 4; and X =...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…As young research enthusiasts in this vast field, our group is exploring the fundamental and application realm of SCO materials. Ranging from monomeric manganese­(III)-based SCO systems to multifunctional SCO-active iron­(II)-based luminescent polymers , and mononuclear, dinuclear, and 1D coordination polymers of cobalt­(II), we are exploring the stimuli-responsive SCO systems. We are further taking a leap into addressing the lesser-known or unexplored areas in this vast field.…”
Section: Molecular Spin Crossover Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…As young research enthusiasts in this vast field, our group is exploring the fundamental and application realm of SCO materials. Ranging from monomeric manganese­(III)-based SCO systems to multifunctional SCO-active iron­(II)-based luminescent polymers , and mononuclear, dinuclear, and 1D coordination polymers of cobalt­(II), we are exploring the stimuli-responsive SCO systems. We are further taking a leap into addressing the lesser-known or unexplored areas in this vast field.…”
Section: Molecular Spin Crossover Systemsmentioning
confidence: 99%
“…Additionally, we have reported for the first time the incorporation of a redox-active motif (EDOT) into the terpyridine system to investigate the SCO characteristics in the cobalt­(II) center (Figure a) . Similarly, several Mn­(III) complexes incorporating an azobenzene motif in the hexadentate Schiff base ligand and different counteranions to study the spin-state switching of the complexes (Figure b–d) are a few milestones achieved in the SCO field.…”
Section: Molecular Spin Crossover Systemsmentioning
confidence: 99%
“…Accordingly, we ended up with a series of five mononuclear manganese( iii ) complexes [Mn(X-sal 2 -323)](ReO 4 ) (X = 5-Cl, ( 27 ); X = 5-Br, ( 28 ); X = 3,5-Cl, ( 29 ); X = 3,5-Br, ( 30 ); and X = 5-NO 2 , ( 31 )). 201 All the complexes have a crystal structure comprising the [Mn(X-sal 2 -323)] + cation and the ReO 4 − anion. To obtain better insight into the effect of cooperativity on the spin crossover properties, careful analysis of the intermolecular interactions between the cationic and anionic unit depicted strong interactions coming from the N–H⋯Z and C–X⋯Z moiety among the cationic unit [Mn(X-sal 2 -323)] + and the counter anion ( Z ).…”
Section: Stimuli-responsive Spin-state Switchingmentioning
confidence: 99%
“…32 was the first ever cyanide-bridged mixed valence [Fe 2 Fe 2 ] square with thermo- and photoinduced SCO, where iron( ii ) centres with an N 6 environment showed spin-state switching between the Fe II LS (S = 0) and Fe II HS (S = 2) state. 201 Although most of the [Fe 2 Co 2 ] squares, using a similar synthesis strategy, undergo MMET between iron and cobalt centres, whereas [Fe 2 Fe 2 ] square moieties in a similar environment prefer to exhibit spin-state switching. 201–212 Even before this ground-breaking work by Lescouëzec et al , Oshio et al and Real et al reported iron( ii ) based cyanide bridged molecular squares showing SCO behaviour using diamagnetic iron( ii ) building blocks.…”
Section: Stimuli-responsive Spin-state Switchingmentioning
confidence: 99%
See 1 more Smart Citation